Pengaruh Pupuk Organik Curah dan Pelet terhadap Pertumbuhan, Produksi, Efisiensi Pemupukan dan Kesehatan Tanaman Jahe - Agus Runhayat (Pusat Penelitian dan Pengembangan Perkebunan, 2014)
The need for inorganic fertilizer and organic ginger cultivation is quite high and become an obstacle when the price off fertilizer is expensive. Another constraint is the attack of bacterial wilt disease. Organic fertilizers on the market have not be enable to overcome these problems. While, organic fertilizer for the cultivation of ginger must have a minimum of three main components, namely as a source of nutrients, C-organic and controlling the disease. Bulk-concentrate organic fertilizer formulation (COFF) and pellets (POF) has been made in Bogor from April to July 2010. Testing of those fertilizer formulation on ginger were conducted in Cicurug Experimental Station, Sukabumi, West Java from August 2010 to June 2012. The purpose of the research was to determine the influence of COFF and POF to the growth, production, inorganic fertilizer efficiency and plant health on big-white ginger. Big-white ginger were planted in polybags. The research was arranged in factorially-randomized block design, repeated three times. The first factor wasapplication of concentrate-organic fertilizer (0; 1,500 g plant-1 COFF and 150 g plant-1 POF), and the second factor was the application of an-organic fertilizer (0; 70; and 80% of the recommended dosage of urea, SP-36 and KCl). Results of the study showed that application of COFF and pellets POF each of as many as 1,500 and 150 g plant-1 can increase growth, yields and quality of ginger rhizome as well as reducing the use of inorganic fertilizers by 30%. Application of COFF in combination with 70% dose of inorganic fertilizer could produce fresh rhizome weight of 1447,40 g plant-1, and 10% of death plant caused by bacterial wilt infestation. Giving of POF as much as 150 g plant-1 plus a 70% dose of inorganic fertilizer could produce fresh rhizome weight of 951.16 g plant-1, and 10.67% of death plant caused by bacterial wilt infestation. Granting COFF or POF without inorganic fertilizer produce fresh rhizome weights about 1115.94 and 591.73 g plant-1 (in-organic fertilizer savings of 100%). Key